Reforming Copyright in the Context of Exercise of the Human Right to Free Expression on the Internet: An Actual Problems of the Modern International Legal Politics - Irina V. Shugurova; Mark V. Shugurov (Centre for Behaviour and Wellness Advocacy, 2015)
The authors discuss major trends in the area of reforming of copyright in the light of full exercise of internationally recognized human right to expression regarding the digital environment, especially the Internet, and demonstrate the significant situation when intellectual property rights, mainly author's exclusive rights, build a lot of troubles for the information human rights. The article also looks at the changes in the understanding the relation between copyright and the human right to freedom of expression and information on the Internet. Much attention is paid to new moments in the modern doctrine of intellectual property that is inspired by process of digitization of author's rights. There is conducted the approach to addressing copyright as one of the digital human rights resulted from property rights and right of creators to protection of their moral and economic interests. However, authors of the article departure from postulate that copyright is the human rights to a certain degree only. Moreover, this article examines the international legal approach to seeking the balance between the human right to freedom of expression, opinion and information, on the one hand, and copyright, especially as regards the Internet, on the other hand. There has been argued that key role in elaborating and adopting the principled standards in this sphere belongs to international law, including international law of human rights. In addition, the latter, as authors have ascertained, must correspond to international law of intellectual property rights, international information law, and international competition law. The study focus on various aspects of solving the problem of adapting copyright to the digital environment.